Interferon-λs and Plasmacytoid Dendritic Cells: A Close Relationship - Finotti, Giulia; Tamassia, Nicola; Cassatella, Marco A. (Frontiers in Immunology, 2017)
Interferon lambdas (IFNλs) are recently discovered cytokines acting not only at the first line of defense against viral infections but also at the mucosal barriers. In fact, a peculiar feature of the IFNλ system is the restricted expression of the functional IFNλR, which is known to be limited to epithelial cells and discrete leukocyte subsets, including the plasmacytoid dendritic cells (pDCs). In the latter case, current data, discussed in this minireview, indicate that IFNλs positively regulate various pDC functions, including pDC expression of interferon-dependent gene (ISG) mRNAs, production of cytokines, survival, and phenotype. Although the knowledge of the effects on pDCs by IFNλs is still incomplete, we speculate that the peculiar pDC responsiveness to IFNλs provide unique advantages for these innate immune cells, not only for viral infections but also during autoimmune disorders and/or tumors, in which pDC involvement and activation variably contribute to their pathogenesis.